Analysis of information risk management methods - Zudin, Rodion (2014)
Zudin, Rodion Analysis of information risk management methods Jyväskylä: University of Jyväskylä, 2014, 33 p. Information Systems, Bachelor’s Thesis Supervisor: Siponen, Mikko A brief overview in the information risk management field is done in this study by introducing the shared terminology and methodology of the field using literature overview in the first chapter. Second chapter consists of examining and comparing two information risk management methodologies proposed by two different guides: Risk Management Guide for Information Technology Systems by National Institute of Standards and Technology and The Security Risk Management Guide by Microsoft. By finding common factors and methods shared by both guides, their shared approach for the information risk management is attempted to be defined.